Electrocoagulation System Design for Wastewater Treatment Optimization: Desain Sistem Elektrokoagulasi untuk Optimalisasi Pengolahan Air Limbah - Aruwanto Hidayat; Syamsudduha Syahrorini Arifianto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Wastewater treatment is a critical process in maintaining environmental sustainability, particularly in reducing contaminants in industrial effluents. Specific Background Electrocoagulation has emerged as a promising method for removing pollutants such as suspended solids and chemical contaminants through electrochemical processes. Knowledge Gap However, integration between system design parameters and performance evaluation in practical applications remains limited. Aims This study aims to design and analyze an electrocoagulation system and evaluate its operational parameters for wastewater treatment. Results The findings show that parameter variations such as voltage, current, and electrode configuration significantly affect treatment performance, including reductions in pollutant indicators. Novelty This research presents a system-level approach combining electrical design and treatment evaluation within a single framework. Implications The results provide a reference for developing efficient and applicable electrocoagulation systems in wastewater treatment processes. Keywords: Electrocoagulation, Wastewater Treatment, Electrical System Design, Process Parameters, Water Quality Key Findings Highlights Electrical parameter variation determines treatment performance Pollutant reduction achieved through electrochemical mechanism System configuration supports practical wastewater processing